MINNESOTA LEGISLATIVE UPDATE AS REPORTED BY WAYNE COX (MCTJ). - HAHN S (Tufts Archival Research Center, 2007)
Copy; Legislative update memorandum on the Minnesota cigarette tax. Shows that the House adopted a tax bill with no increase in cigarette tax. Discusses the postponement of a vote on cigarette tax in the Senate and the potential that bill may be dropped.